Agronomic assessment of phosphorus efficacy for potato (Solanum tuberosum L) under legume intercrops - Gitari, H.I.; Nyawade, S.; Kamau, S.; Karanja, N.; Gachene, C.K.K.; Schulte-Geldermann, Elmar (Informa UK Limited, 2020)
Phosphorus (P) is an essential element and its efficient use is of global importance. This study evaluated the effect of growing potato under legume intercrops on P uptake and use efficiency indices: P harvest index (PHI), P uptake efficiency (PuPE), P partial factor productivity (PPFP) and P partial balance (PPB). The experiment was carried out for four consecutive seasons with treatments comprising potato cultivated under legume intercrops: none (T1), dolichos (Lablab purpureus L) (T2), peas (Pisum sativum L) (T3) and beans (Phaseolus vulgaris L) (T4). Across the seasons, the mean haulm P uptake for T2 (6.7 kg P ha−1), T4 (5.5) and T3 (4.5) were 6%, 23% and 36% lower than that observed in T1 (7.1 kg P ha−1), respectively. On the other hand, tuber P uptake was highest in T1 (21.8 kg P ha−1) and T2 (21.3 kg P ha−1) and were significantly higher than 13.2 kg P ha−1 in T3 and 15.1 kg P ha−1 in T4. This had a profound effect on PuPE, which was equally highest in T1 (0.26 kg total P uptake kg−1 P supply) and T2 (0.25) and lowest in T3 (0.16) and T4 (0.18). Similarly, PPFP, PHI and PPB followed a similar trend, with highest values in T1 (57 kg tuber dry matter yield kg−1 P supply, 76.4 kg tuber P uptake kg−1 total plant’s P uptake and 0.20 kg tuber P uptake kg−1 P supply, respectively). Among the tested legume intercrops, dolichos competed least for P with the main crop (potato) hence it can be integrated into potato-based cropping systems without compromising potato tuber yield.